2020
DOI: 10.1016/j.molp.2019.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase HDA9 and WRKY53 Transcription Factor Are Mutual Antagonists in Regulation of Plant Stress Response

Abstract: Epigenetic regulation of gene expression is important for plant adaptation to environmental changes. Previous results showed that Arabidopsis RPD3-like histone deacetylase HDA9 is known to function in repressing plant response to stress in Arabidopsis. However, how HDA9 targets to specific chromatin loci and controls gene expression networks involved in plant response to stress remains largely unclear. Here, we show that HDA9 represses stress tolerance response by interacting with and regulating the DNA bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 55 publications
4
67
0
Order By: Relevance
“…The transcription factors WRKY53 ( Chen et al , 2016 ; Zheng et al , 2020 ), ABI4, ABI3 ( Baek et al , 2020 , Khan et al , 2020 ), and HY5 ( Yang et al , 2020 ), the epigenome readers VP1/ABI3-LIKE 1 (VAL1) and VAL2 ( Zeng et al , 2020 ), the circadian clock Evening Complex (EC) transcription factor(s) ELF3 and possibly LUX ( Lee et al , 2019 ; Park et al , 2019 ), and AT-hook motif-containing protein AHL22 ( Yun et al , 2012 ) are currently the only confirmed HDA9-interacting proteins with DNA binding capacity ( Fig. 1 ).…”
Section: Hda9-interacting Proteins; the Hda9–hos15–pwr Core Hdac Compmentioning
confidence: 99%
See 4 more Smart Citations
“…The transcription factors WRKY53 ( Chen et al , 2016 ; Zheng et al , 2020 ), ABI4, ABI3 ( Baek et al , 2020 , Khan et al , 2020 ), and HY5 ( Yang et al , 2020 ), the epigenome readers VP1/ABI3-LIKE 1 (VAL1) and VAL2 ( Zeng et al , 2020 ), the circadian clock Evening Complex (EC) transcription factor(s) ELF3 and possibly LUX ( Lee et al , 2019 ; Park et al , 2019 ), and AT-hook motif-containing protein AHL22 ( Yun et al , 2012 ) are currently the only confirmed HDA9-interacting proteins with DNA binding capacity ( Fig. 1 ).…”
Section: Hda9-interacting Proteins; the Hda9–hos15–pwr Core Hdac Compmentioning
confidence: 99%
“…1 ). In particular, the molecular mechanism of the HDA9–WRKY53 interaction is now understood in detail ( Zheng et al , 2020 ). Despite the limited number of confirmed HDA9 interactors, it is likely that HDA9 associates directly—or as part of a bigger HDAC multiprotein complex—with many more yet to be discovered DNA-binding factors.…”
Section: Hda9-interacting Proteins; the Hda9–hos15–pwr Core Hdac Compmentioning
confidence: 99%
See 3 more Smart Citations